TIM-4 in macrophages contributes to nasal polyp formation through the TGF-β1–mediated epithelial to mesenchymal transition in nasal epithelial cells - Qin, Danxue; Liu, Peiqiang; Zhou, Huiqin; Jin, Jing; Gong, Wanyang; Liu, Kunyu; Chen, Siyuan; Huang, Jingyu; Fan, Wenjun; Tao, Zezhang; Xu, Yu (Frontiers in Immunology, 2022)
Chronic rhinosinusitis with nasal polyps (CRSwNP) is caused by prolonged inflammation of the paranasal sinus mucosa. The epithelial to mesenchymal transition (EMT) is involved in the occurrence and development of CRSwNP. The T-cell immunoglobulin domain and the mucin domain 4 (TIM-4) is closely related to chronic inflammation, but its mechanism in CRSwNP is poorly understood. In our study, we found that TIM-4 was increased in the sinonasal mucosa of CRSwNP patients and, especially, in macrophages. TIM-4 was positively correlated with α-SMA but negatively correlated with E-cadherin in CRS. Moreover, we confirmed that TIM-4 was positively correlated with the clinical parameters of the Lund-Mackay and Lund-Kennedy scores. In the NP mouse model, administration of TIM-4 neutralizing antibody significantly reduced the polypoid lesions and inhibited the EMT process. TIM-4 activation by stimulating with tissue extracts of CRSwNP led to a significant increase of TGF-β1 expression in macrophages in vitro. Furthermore, coculture of macrophages and human nasal epithelial cells (hNECs) results suggested that the overexpression of TIM-4 in macrophages made a contribution to the EMT process in hNECs. Mechanistically, TIM-4 upregulated TGF-β1 expression in macrophages via the ROS/p38 MAPK/Egr-1 pathway. In conclusion, TIM-4 contributes to the EMT process and aggravates the development of CRSwNP by facilitating the production of TGF-β1 in macrophages. Inhibition of TIM-4 expression suppresses nasal polyp formation, which might provide a new therapeutic approach for CRSwNP.